2016
DOI: 10.1155/2016/5798068
|View full text |Cite
|
Sign up to set email alerts
|

Client Satisfaction with Delivery Care Service and Associated Factors in the Public Health Facilities of Gamo Gofa Zone, Southwest Ethiopia:In a Resource Limited Setting

Abstract: Background. Ensuring patient satisfaction is an important means of secondary prevention of maternal mortality. This study presents findings from a multidimensional study of client satisfaction from the Gamo Gofa Zone in Southwest Ethiopia. Methods. A facility based cross-sectional study using exit interviews was conducted from 2014. Client satisfaction was measured using a survey adopted from the Donabedian quality assessment framework. Thirteen health institutions were randomly sampled of 66 institutions in G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
57
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 14 publications
11
57
10
1
Order By: Relevance
“…This finding was lower than the study done in Oromia Region Asella Hospital which was 80.7% [29], and Gamogofa 79.1% [30] but higher than Amhara region, 61.9% [31]. The deference may be due to the fact the Addis Ababa is big city in which more staffed, motivated service providers and equipped facility.…”
Section: Discussioncontrasting
confidence: 55%
“…This finding was lower than the study done in Oromia Region Asella Hospital which was 80.7% [29], and Gamogofa 79.1% [30] but higher than Amhara region, 61.9% [31]. The deference may be due to the fact the Addis Ababa is big city in which more staffed, motivated service providers and equipped facility.…”
Section: Discussioncontrasting
confidence: 55%
“…The study revealed that, the overall delivery service satisfaction of mothers was 82.1%. This finding is comparable with studies conducted at Serbian public Hospitals (81%), Wolaita Hospital, Ethiopia (82.3%), Assela hospital Ethiopia (80.7%), Gamo-Gofa Zone, South Ethiopia (79.1%) and Debremarkos Hospital, North west Ethiopia 81.7% [22][23][24][25][26].This may be due to similarities of these hospitals by patient load, number of health professionals and infrastructures.…”
Section: Discussionsupporting
confidence: 80%
“…The proportion of caretakers satisfaction in current finding was lower than many other studies in Ethiopia: four major regions (82.9%) [26], Arba Minch in south (90.2%) [29], Jimma in south west (79.4%) [40], Gamo Gofa in south (79.1%) [41], Debre Markos in North (81.7%) [42], West-Arsi in central (74.6%) [31], and Wolaita in south west (82.9%) [32]. The difference might be due to difference in sample size and study population as this study used only population at community level, and the disparities in socio-economic status of the respondents and level of health facilities.…”
Section: Discussioncontrasting
confidence: 74%